2009
DOI: 10.1002/elan.200804406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Glutathione, Surface Active Agents, and Ionic Strength on the Detection of Metallothioneins by Using of Brdicka Reaction

Abstract: We investigated the effects of two surface active agents (sodium dodecyl sulfate, SDS, and polyoxyethylene sorbitol, , ionic strength and reduced glutathione (GSH) on MT signals measured by adsorptive transfer stripping differential pulse voltammetry Brdicka reaction. If we compared the GSH and MT signals at the accumulation time of 120 s, the MT signal was more than two hundred times higher than the GSH one. The influence of Tween-20 was investigated in a broad concentration range (from 10 À8 to 10 À11 %, v/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The concentration of MT and cisplatin used in this study was similar to those found in the body, where the concentrations of these compounds ranges from sub-units to units μM [11,21,64,65]. Concerning our findings, we have discovered that a new signal appeared after MT-cisplatin interaction, which correlated well both with time of interaction and concentration of the drug.…”
Section: Discussionsupporting
confidence: 81%
“…The concentration of MT and cisplatin used in this study was similar to those found in the body, where the concentrations of these compounds ranges from sub-units to units μM [11,21,64,65]. Concerning our findings, we have discovered that a new signal appeared after MT-cisplatin interaction, which correlated well both with time of interaction and concentration of the drug.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, low-molecular mass thiols (cysteine, glutathione and SH-rich peptides), which can be hardly denatured by heat treatment, can interfere with electrochemical MT determination too [92]. Nevertheless, we proved that both low molecular thiols and non-heateddegradable proteins did not interfere the Brdickas measurements [24]. Surface active compounds present in biological samples can influence the adsorption of the analytes onto the electrode surface, however it was shown that the influence is minimal in this type of a solution [24].…”
Section: Sodium-dodecyl Sulfate Polyacrylamide Gel Electrophoresismentioning
confidence: 82%
“…Nevertheless, we proved that both low molecular thiols and non-heateddegradable proteins did not interfere the Brdickas measurements [24]. Surface active compounds present in biological samples can influence the adsorption of the analytes onto the electrode surface, however it was shown that the influence is minimal in this type of a solution [24].…”
Section: Sodium-dodecyl Sulfate Polyacrylamide Gel Electrophoresismentioning
confidence: 95%
“…For more details on adsorption of thiols on the surface of mercury electrodes, see previous studies [17,21,22]. Thanks to the free ÀSH moiety, GSH is a highly electroactive molecule, but its low molecular mass negatively influences adsorption on a working electrode surface [23]. In spite of this drawback, it is possible to study even such a small molecule by this method (Fig.…”
Section: Resultsmentioning
confidence: 97%